Legal Construction of Dispute Resolution Mining Land Overlapping with Plantation Land - Halim, Arivan (Indonesian Journal of Multidisciplinary Science, 2023)
Indonesian Agrarian Law recognizes the principle of horizontal separation which has consequences for classifying land rights. One of the granting and acquisition of land rights can be given to mining and plantation businesses. Even so, the granting of land rights to these two types of businesses still generates a lot of disputes . The dispute that occurred was overlapping in the granting of business licenses to mining businesses and/or plantation businesses, based on State Administration decisions issued by State Administration Officials that were not in accordance with statutory regulations and did not heed the General Principles of Good Governance in particular the principle of precision. The purpose of this scientific work is to provide a legal construction for resolving disputes over overlapping mining land and plantation land. The author uses a way of reviewing the applicable laws and regulations, existing theories and principles critically and systematically. The legal constructions offered are civil lawsuit to request compensation through the District Court to the State Administrative Officer who made the State Administrative Decision after the issuance of the State Administrative Court Decision which has a ruling granting the claim to cancel the State Administrative Decision which caused losses and has permanent legal force.